Expression, purification, crystallization and preliminary crystallographic analysis of a GH20 β-N-acetylglucosaminidase from the marine bacterium Vibrio harveyi - Meekrathok, Piyanat (International Union of Crystallography, 2015)

(untitled) (Acta Crystallogr F Struct Biol Commun)
Vibrio harveyi β-N-acetylglucosaminidase (VhGlcNAcase) is a new member of the GH20 glycoside hydrolase family responsible for the complete degradation of chitin fragments, with N-acetylglucosamine (GlcNAc) monomers as the final products. In this study, the crystallization and preliminary crystallographic data of wild-type VhGlcNAcase and its catalytically inactive mutant D437A in the absence and the presence of substrate are reported. Crystals of wild-type VhGlcNAcase were grown in 0.1 M sodium acetate pH 4.6, 1.4 M sodium malonate, while crystals of the D437A mutant were obtained in 0.1 M bis-tris pH 7.5, 0.1 M sodium acetate, 20% PEG 3350. X-ray data from the wild-type and the mutant crystals were collected at a synchrotron-radiation light source and were complete to a resolution of 2.5 Å. All crystals were composed of the same type of dimer, with the substrate N,N′-diacetylglucosamine (GlcNAc(2) or diNAG) used for soaking was cleaved by the active enzyme, leaving only a single GlcNAc molecule bound to the protein.